Phosphorylation of the Bacillus subtilis Replication Controller YabA Plays a Role in Regulation of Sporulation and Biofilm Formation - García García, Tránsito; Ventroux, Magali; Derouiche, Abderahmane; Bidnenko, Vladimir; Correia Santos, Sara; Henry, Céline; Mijakovic, Ivan; Noirot-Gros, Marie-Françoise; Poncet, Sandrine (Frontiers in Microbiology, 2018)
Bacillus subtilis cells can adopt different life-styles in response to various environmental cues, including planktonic cells during vegetative growth, sessile cells during biofilm formation and sporulation. While switching life-styles, bacteria must coordinate the progression of their cell cycle with their physiological status. Our current understanding of the regulatory pathways controlling the decision-making processes and triggering developmental switches highlights a key role of protein phosphorylation. The regulatory mechanisms that integrate the bacterial chromosome replication status with sporulation involve checkpoint proteins that target the replication initiator DnaA or the kinase phosphorelay controlling the master regulator Spo0A. B. subtilis YabA is known to interact with DnaA to prevent over-initiation of replication during vegetative growth. Here, we report that YabA is phosphorylated by YabT, a Ser/Thr kinase expressed during sporulation and biofilm formation. The phosphorylation of YabA has no effect on replication initiation control but hyper-phosphorylation of YabA leads to an increase in sporulation efficiency and a strong inhibition of biofilm formation. We also provide evidence that YabA phosphorylation affects the level of Spo0A-P in cells. These results indicate that YabA is a multifunctional protein with a dual role in regulating replication initiation and life-style switching, thereby providing a potential mechanism for cross-talk and coordination of cellular processes during adaptation to environmental change.